2017
DOI: 10.3390/s17051175
|View full text |Cite
|
Sign up to set email alerts
|

A Stretchable Electromagnetic Absorber Fabricated Using Screen Printing Technology

Abstract: A stretchable electromagnetic absorber fabricated using screen printing technology is proposed in this paper. We used a polydimethylsiloxane (PDMS) substrate to fabricate the stretchable absorber since PDMS exhibits good dielectric properties, flexibility, and restoring capabilities. DuPont PE872 (DuPont, Wilmington, CT, USA), a stretchable silver conductive ink, was used for the screen printing technique. The reflection coefficient of the absorber was measured using a vector network analyzer and a waveguide. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(6 citation statements)
references
References 39 publications
(46 reference statements)
0
6
0
Order By: Relevance
“…[ 7 ] Although many studies are focused on microwave‐invisible materials, only a limited stretchable strategies have been proposed by far. [ 1h,8 ] A few researchers have successfully integrated the ECPs with the stretchable elastomers, which avails the device with a certain extend of stretchability. However, this adaptation introduces new shortcomings.…”
Section: Introductionmentioning
confidence: 99%
“…[ 7 ] Although many studies are focused on microwave‐invisible materials, only a limited stretchable strategies have been proposed by far. [ 1h,8 ] A few researchers have successfully integrated the ECPs with the stretchable elastomers, which avails the device with a certain extend of stretchability. However, this adaptation introduces new shortcomings.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, its fabrication is easy and involves low cost. Therefore, metamaterial absorbers have been researched in various electromagnetic fields such as stealth technology [35,36], electromagnetic interference/electromagnetic compatibility [37,38], or radio frequency (RF) sensor applications [39,40].…”
Section: Introductionmentioning
confidence: 99%
“…Besides the innovation in hybrid absorbent materials development for achieving high performance (broad absorption band and light weight , ), researchers have also focused on the design of their micro/nanostructures. It has been concluded that materials with porous or hollow nanostructure may enhance the EM-wave-absorbing capability because of polarization and multireflection. Furthermore, recent progress in light-weight, flexibile, or even stretchable EM-wave-absorbing materials has gained considerable attention. , Jeong and Lim proposed a stretchable EM absorber fabricated using screen printing technology. Jung et al fabricated a stretchable and transparent layer with a silver nanowire percolation network on an elastic poly­(dimethylsiloxane) substrate for EM-wave shielding.…”
Section: Introductionmentioning
confidence: 99%